Antimetastatic Activity of Gallic Acid‐conjugated Chitosan against Pulmonary Metastasis of Colon Carcinoma Cells. (28th December 2017) - Lee, Hye Lim; Choi, Cheol Woong; Kim, Jungsoo; Cha, Byungyoul; Nah, Jae Woon; Hong, Jeong Sup; Hwang, Sung Chul; Jeong, Young‐IL; Kang, Dae Hwan
Abstract : We synthesized gallic acid (GA)‐conjugated chitosan (abbreviated as chitogallate) to study its antitumor activity against CT26 mouse colorectal carcinoma cells. GA was conjugated with chitosan by aid of water‐soluble carbodiimide. Chitogallate nanoparticles were prepared by dialysis method, and these nanoparticles have spherical shapes with sizes ranged about 70–250 nm. Chitogallate nanoparticles have superior antioxidants activities as well as GA itself. At cytotoxicity study, GA showed dose‐dependent cytotoxicities against CCD986sk cells and CT26 cells while chitogallate nanoparticles were not significantly affected to the viability of cells. In Matrigel invasion assay, chitogallate nanoparticles have superior anti‐invasive capacity against cancer cells as well as GA itself, i.e ., invasiveness of CT26 cells was decreased according to GA contents in chitogallate nanoparticles. Furthermore, gelatin zymography also showed that chitogallate nanoparticles having higher substitution degree of GA decreased matrix metalloproteinase‐2 activity. Chitogallate nanoparticles efficiently inhibited pulmonary metastasis of CT26 cells in animal pulmonary metastasis model. We prepared chitogallate nanoparticles for application as an anti‐invasive agent. Chitogallate nanoparticles were less toxic than GA itself and have superior anti‐invasive/antimetastatic activity. We suggest that chitogallate nanoparticles are promising candidate for inhibition of tumor invasion/metastasis. Abstract : Gallic acid‐conjugated chitosan (chitogallate) conjugates were synthesized as an anticarcinogenic agent to inhibit invasion and migration of cancer cells. Chitogallate nanoparticles were properly inhibited invasion and matrix metalloproteinase (MMP)‐2 activity of CT26 cells. Chitogallate nanoparticles also showed higher antimetastatic activity than GA itself.